Morphological variation and haplotype diversity of \(Halimeda macroloba\) and \(H. opuntia\) (Chlorophyta: Halimedaceae) from Southern Vietnam - Nguyen, Trung Hieu; Nguyen Nhat, Nhu Thuy; Nguyen, Xuan Thuy; Nguyen, Vy Xuan (Vietnam Journal of Marine Science and Technology, 2022)
Plasticity in morphology is a common phenomenon of aquatic plants. Halimeda (Chlorophyta: Halimedaceae) is usually supersaturated with calcium carbonate and is found in tropical and subtropical regions. Among members of Halimeda, both species including Halimeda macroloba and H. opuntia, often occur in different habitats. Haplotype diversity and network of Halimeda were reported in the different sea and oceanic systems. However, there are no reports of the genetic diversity of Halimeda in Vietnamese waters. This present study carried out sample collections along the coast of Southern Viet Nam, including the coast sites, offshore islands, and Spratly (Truong Sa) islands. External morphological and anatomical characteristics of two dominant species, Halimeda macroloba and H. opuntia, were caparisoned. The genetic marker tufA was applied to find the haplotype diversity and network among Vietnamese and worldwide populations. The results showed that high morphology exists in both species. In contrast, the genetic variation in H. macroloba is very low, and H. opuntia tends to form a distinct group. We suggest that more samples of two species from other locations in Northern Vietnam be included.